ALASAN TURKI MELAKUKAN KERJASAMA DENGAN SOMALIA PADA TAHUN 2017 - Ramadhani Maghfirah; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This Scription provides an explanation of Turkey's efforts to expand the influence of its power in the African region in Mogadishu Somalia in 2017. The purpose of this study is to find out the causes of why Turkey is cooperating with Somalia. This research method uses qualitative research methods by conducting literature studies. To answer the purpose of the study the author uses the perspective of behaviorealism with the foreign policy theory put forward by Gideon Rose in 1998. In this case the factors that cause foreign policy of a country are influenced by ideational factors in which Turkey cooperates with affected Somalia by the influence of the AKP party government. The second, from the influence of the relative material strength that is with Turkey with the world's sixth strongest military must expand its power. Third, the influence of a long-term grand strategy in looking at the potential of strategic regions and the potential of Somali energy resources. Finally, the influence of the elite's threat preference which influences the threat of China and Saudi Arabia which also broadens its influence in the African Region. Turkey to achieve the highest level of cooperation with Somalia first requires a low political cooperation in the form of humanitarian assistance, infrastructure development, and education so that the highest level of cooperation can be achieved by establishing a military base in Mogadishu Somalia in 2017 Key Words: Turkey, Somalia, Behaviorealisme, Foreign Policy, Low Politic